2021
DOI: 10.1002/anie.202107480
|View full text |Cite
|
Sign up to set email alerts
|

Selective Bond Cleavage in RAFT Agents Promoted by Low‐Energy Electron Attachment

Abstract: Radical polymerization with reversible addition‐fragmentation chain transfer (RAFT polymerization) has been successfully applied to generate polymers of well‐defined architecture. For RAFT polymerization a source of radicals is required. Recent work has demonstrated that for minimal side‐reactions and high spatio‐temporal control these should be formed directly from the RAFT agent or macroRAFT agent (usually carbonothiosulfanyl compounds) thermally, photochemically or by electrochemical reduction. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…It was further reported that the energy required to induce the dissociation of Br − (0.55 eV) from BrU − is less compared to Cl − (0.87 eV) and F − (2.25 eV) from the respective halouracil anions. These results indicate that the release of the halogen anion from 5-FU − is less favorable compared to other halouracils and FU is not susceptible to the electron-induced decomposition with electron energy close to zero eV, which may attach with high cross-sections [ 33 , 34 ]. On the other hand, the calculated threshold for FU indicates that F − formation should be possible above the electron energy of 1.80 eV [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was further reported that the energy required to induce the dissociation of Br − (0.55 eV) from BrU − is less compared to Cl − (0.87 eV) and F − (2.25 eV) from the respective halouracil anions. These results indicate that the release of the halogen anion from 5-FU − is less favorable compared to other halouracils and FU is not susceptible to the electron-induced decomposition with electron energy close to zero eV, which may attach with high cross-sections [ 33 , 34 ]. On the other hand, the calculated threshold for FU indicates that F − formation should be possible above the electron energy of 1.80 eV [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The excited species [L 2 B ] +* ( E 1/2 ([L 2 B ] + * /[L 2 B ] • ) = 1.27 V vs SCE in DMSO) could oxidize [ B (Cat) 2 ] − ( E 1/2 ([ B (Cat) 2 ] • /[ B (Cat) 2 ] − ) = 0.45 V, Table S4 and Figure S61), indicating that the process of ion-pair electron transfer was feasible under light excitation. After IP-ISET of [L 2 B ] + [ B (Cat) 2 ] − , the produced [L 2 B ] • acted as the reductant, instead of [L 2 B ] +* as the reductant ( vide infra ), to reduce CTA to obtain the chain-initiated radical, [ZCS 2 ] − , and ground-state [L 2 B ] + . The chain-initiated radical reacted with a monomer to produce P n • , achieving chain propagation.…”
Section: Resultsmentioning
confidence: 99%
“…The EA of NA is close to the EA of 0.45 eV for the other recently investigated molecule, (CH 3 S) 2 CS, for which the parent anion was observed. 48 Hence, it may be proposed that for NA, the formation of the stable parent anion is possible but due to the low efficiency of this process, the anion yield is below the detection limit of the apparatus. The electron attachment resonance positions were determined by fitting Gaussian peaks to the experimental data, whereas the anion appearance energy (AE) was estimated using the procedure described by Meißner et al in ref.…”
Section: Resultsmentioning
confidence: 99%